Treatability ofTropical Wood Using Newly Synthesized Organotin(IV) Complexes - Jusoh, Ismail; Rahman, Md. Masudur; Affan, Md. Abu; Hamdan, Sinin; Salam, Md. Abdus (Journal of Applied Sciences, 2012)
The treatability ofthree tropical wood species namely Alstonia scholar is (pulai), Macaranga triloba (mahang) and Hevea brasiliensis (rubberwood) was investigated Wood species were chemically treated with five newly synthesized organotin(lV) complexes using full-cell treatment method This study explored whether tropical wood species could be treated successfully with newly synthesized organotin(IV) complexes as wood preservatives. Ten 19x19x19 mm sized wood cubes of each species were treated with three levels of concentration (0.1, 0.5 and 1 %) ofmono me thyltin (IV) (MMI') andmonophenyltin(IV) (MPT) ofmono series and dimethyltin(IV) (DMT), diphenyltin(IV) (DPT) and dibulyltin(IV) (DBT) ofdiseries organotin(IV) complexes with 2-acetylpyridine-N (4)-cyclohexyl thiosemicarbazone ligand The treated wood species were evaluated by chemical retention values and characterized by FT -IR (Fourier Transform Infrared) spectroscopy analysis. The highest retention (10.59 kg m-1) was found in Alstonia scholaris treated with 1% DMT complexes and the lowest retention (0.47 kg m -') was found inHevea brasiliensis treated with OJ % DMT complexes. FT -IR spectra oftreated wood showed new absorption bands in the range of 594-606 and 441-457 em-I due to Sn-C and Sn-N bonds, respectively. A newly formed absorption band at range 549-569 cm-1 due to Sn-O band was also observed in the treated wood sample spectra. Chemical retention and FTIR spectra suggest tropical wood species are treatable with newly synthesized organotin(IV) complexes as wood preservatives.